Pendampingan Pengembangan Bahan Ajar Program IbM Komunitas Ibu Belajar Matematika - Dewi Wahyuning Hikmah; Darwin Djeni; Nur Fitri Amalia; Shofiyatul Hasanah (TAAWUN, 2022)
This assistance is one of the stages of the community service program carried out by a group of lecturers. This program is in the form of training and mentoring for the mother community to learn Mathematics. Referring to the results of PISA in 2009 that the ability of Indonesian students in general is poor in solving math problems. Most students think that Mathematics is difficult to learn and lack of parental support to help students learn. The purpose of this assistance is to prepare Mathematics learning books. This study material book was prepared as a guidebook for the implementation of the IbM Community Mathematics Learning Mothers Community training and mentoring program in elementary schools which was carried out for approximately one semester. With this textbook, it is hoped that Mathematics will no longer be a scary subject for students, especially at the elementary school level, but will become an easy, fun, and enjoyable lesson. The results of the mentoring are in the form of teaching materials consisting of 40 essential topics in the elementary school Mathematics Curriculum. The structure of learning materials for each topic begins with concepts, sample questions, exercises, discussions, and answer keys. The textbook is ready to be used for the program.